Pengaruh Marketing Mix Terhadap Kinerja Pemasaran Industri Kecil Menengah Sektor Kontruksi Bengkel Las di Moderasi Kebijakan Pemerintah Pada Masa Pandemi Covid 19 - Satria Tirtayasa; Yeni Ardini Daulay (Magister Manajemen Universitas Muhammadiyah Sumatera Utara, 2021)
This study aims to analyze the effect of the marketing mix (product, price, promotion and location) on the marketing performance of the Small and Medium Industries Construction Sector, Medan City Court Construction Workshop during the Covid 19 pandemic. And to analyze the moderating role of government policies to moderate the effect of the marketing mix (product, price, promotion and location) on the marketing performance of Small and Medium Industries in the Construction Sector of the Medan City Court Welding Workshop during the Covid 19 pandemic. This type of research is survey research, because it takes a sample from one population. This study uses an explanatory research approach, which aims to explain the causal relationship between the research variables and the testing hypothesis. The results showed that the marketing mix (product, price, promotion and location) had a positive and significant effect on the marketing performance of the Small and Medium Industries Construction Sector, Medan City Court Construction Workshop during the Covid 19 pandemic. promotion and location) on the marketing performance of Small and Medium Industries in the Construction Sector, Welding Workshop, Medan City Court during the Covid 19 pandemic